SAT0221 OFF-LABEL USE OF BIOLOGICAL THERAPIES IN RELAPSING AND/OR REFRACTORY POLYARTERITIS NODOSA. (June 2019) - Canzian, Alice; Karadag, Omer; Contis, Anne; Maurier, Francois; Sartorelli, Silvia; Denis, Laure; Sanges, Sebastien; Moreuil, Claire De; Durel, Cécile-Audrey; Durupt, Stephane; Jachiet, Marie; Rouzaud, Diane; et al.
Abstract : Background: Polyarteritis nodosa (PAN) is a rare systemic necrotizing vasculitis of medium- and small-sized arteries, not associated with antineutrophil cytoplasmic antibodies (ANCA). Conventional treatments include glucocorticoids (GCs) for non-severe disease and a combination of GCs and immunosuppressive agents for severe disease. Nevertheless, some patients have refractory and/or relapsing disease. Objectives: We examined the use of off-label biological therapy for relapsing/refractory PAN. Methods: This retrospective European collaborative study included patients with PAN meeting ACR criteria and/or Chapel Hill Consensus Conference 2012 definitions. Treatment efficacy and safety are recorded. Remission was defined as the absence of vasculitis manifestations (BVAS = 0) with a prednisone dose ≤5 mg/day. Partial response was defined as a BVAS = 0 with a prednisone dose between 6 and 10 mg/day. Results: Fifty-one patients (24 men, 27 women; median age 51 years) were included. Eighteen (35%) patients received TNF-alpha blockers, 16 (31%) received rituximab (RTX), 9 (18%) tocilizumab (TCZ), and 8 (16%) other biologics (including alemtuzumab in 3, anakinra in 2, interferon-alpha in 2 and abatacept in one). Previous treatments were: GCs in all cases, including methylprednisolone infusions (72%) and oral GCs (92%), cyclophosphamide (61%), azathioprine (53%), methotrexate (45%) and mycophenolate mofetil (47%). At inclusion, median BVAS was 5 (range 0-18), including 5 (2-12) in the TNF-alpha blockers group, 5 (2-12) in the RTX group and 4 (0-6) in the TCZ group. After median follow-up of 34.4 months (IQR 21.5-59.5), remissions, partial responses and treatment failure, respectively, were noted in 41%, 6% and 53% for TNF-alpha blockers recipients, 25%, 12% and 63% for RTX recipients, and 57%, 0% and 43% for TCZ recipients. No remission was noted in patients treated with anakinra, alemtuzumab and abatacept. Median BVAS dropped to 3 at 6 months, 0 at 12 months and 0 at last follow-up in the TNF-alpha blockers group, to 3.5, 0 and 2 in the RTX group, respectively, and 0, 0 and 0 in the TCZ group. A GC-sparing effect seemed more important with TNF-alpha blockers and TCZ. Median GCs dose decreased from the baseline 15 mg/day to 10 at 6 months, 5 at 12 months and 5 at last follow-up in the TNF-alpha blockers group, from 15 mg/day to 10 at 6 months, 5 at 12 months and 10 at last follow-up in the RTX group, and from 15 mg/day to 7 at 6 months, 5 at 12 months and 5 at last follow-up in the TCZ group. Four (22%) patients stopped TNF-alpha blockers because of allergic reaction in one and refractory disease in 3. Six (38%) stopped RTX because of refractory disease. Finally, 4 (44%) stopped TCZ because of adverse events in 2 (testicular abscess and worsening renal failure) and refractory disease in 2. Conclusion: The results of this study suggest that TNF-alpha blockers and TCZ may achieve higher rates of remission and GC-sparing in relapsing and/or refractory PAN than other biologics. Our data warrant further study to confirm or not these findings. Disclosure of Interests: Alice Canzian: None declared, Omer Karadag: None declared, Anne Contis: None declared, Francois Maurier: None declared, Silvia Sartorelli: None declared, Laure Denis: None declared, Sebastien Sanges: None declared, Claire De Moreuil: None declared, Cécile-Audrey Durel: None declared, Stephane Durupt: None declared, Marie Jachiet: None declared, Diane Rouzaud: None declared, Carlo Salvarani: None declared, Franco Schiavon: None declared, Lorenzo Dagna Consultant for: Prof Lorenzo Dagna received consultation honoraria from Abbvie, Amgen, Biogen, Bristol-Myers Squibb, Celltrion, Novartis, Pfizer, Sanofi-Genzyme, and SOBI., Fabrice Bonnet: None declared, David Jayne Grant/research support from: David Jayne has received research grants from Chemocentryx, GSK, Roche/Genentech and Sanofi-Genzyme. He has received consultancy fees from Astra-Zeneca, Boehringer-Ingelheim, Chemocentryx, Chugai, GSK, Infla-RX, Insmed and Takeda, Loïc Guillevin: None declared, Benjamin Terrier: None declared